THE WAY OF THE FUTURE IN AGRICULTURE: SMART FARMING DRIVEN BY MOBILE APPLICATIONS - Tejbahadur, Singh Atish; B. P. Bhol (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Agriculture is the world's oldest occupation; Agriculture is also India's major occupation with farmers being the backbone of the country. Due to the beginning of the digital revolution on 1st July 2015 by Prime Minister Narendra Modi, today the smartphone usage has risen to 67.7% in the rural markets. Farmers are constantly embracing the availability of smartphones and the internet. The future of farming around the world as well as in India depends on mobile applications, websites and data. Services like Agrometeorological advisory services (AAS) by India Meteorological department (IMD) on the official website of IMD or mobile application of IMD called “Mausam” accessed through smartphones have significantly helped farmers. Services on smartphones like Agrometeorological advisory services (AAS) help farmers to keep themselves informed about the weather and make decisions about their agricultural practices based on weather forecasts. As per study on farmers in Anand District of the state of Gujarat in India, around 80.91% of farmers who adopted services like Agrometeorological advisory services (AAS) reported benefits in terms of crop growth. Farmers also heavily rely on GPS, through GPS farmers can farm precisely on their fields, improve their farm planning, field mapping and operate heavy farm machinery like tractors on their field during foggy weather conditions. Due to growth in the digital era amongst farmers, the Government of India has launched mobile applications like “Kisan Rath”, such applications help farmers to identify transport facilities for agricultural produce. Such mobile applications help farmers to transport their farm products from the direct gates of their farms to market, as well as these applications help better pricing of perishable products. Several other mobile applications like Plantix have been revolutionizing agriculture with the help of Artificial Intelligence (AI), applications like Plantix help farmers to easily identify the problems or diseases their crops are facing with proper solutions. This saves the time of the farmers and minimizes the harm to their crops by providing the information and solutions about the problem on time. Such applications are proving to be revolutionary in the agricultural industry. Plantix has more than 10 million downloads. Gottfried Pessl, CEO of Pessl Instruments, believes that mobile applications and artificial intelligence will be the future of farming in India. These digital tools will improve farming data, yield management, and decision-making, promoting sustainable practices and healthier crops. They will play a significant role globally